Sign of the moon - Hunter, Erin.; McLoughlin, Wayne (New York : Harper, 2011)
As Jayfeather, Lionblaze, and Dovepaw continue trying to understand the mysterious prophecy that binds them, Jayfeather receives a desperate plea for help from the Tribe of the Rushing Water.
Includes instructions for "Warriors adventure game."
"A Working partners book"--Jkt.
Keywords: Cats; Prophecies; Adventure and adventurers; Fantasy